Strategi Guru Akidah Akhlak dalam Mengatasi Perilaku Negatif Peserta Didik MTS - Syarifuddin, Ummah Karimah; Daffa, Tajaufa Maulitaj (Prodi Pendidikan Agama Islam IAINU Kebumen, 2024)
Akidah Akhlak education has an important role in shaping the character of students who are moral and noble. This is a challenge for Akidah Akhlak teachers in implementing the right strategy to overcome the negative behavior of students. The purpose of this study was to determine how the Akidah Akhlak teacher's strategy in Overcoming Negative Behavior of Students at MTs Daarussa'adah Ciganjur South Jakarta, the factors that cause negative behavior of students towards peers at MTs Daarussa'adah Ciganjur South Jakarta and the supporting and inhibiting factors in overcoming negative behavior of students at MTs Daarussa'adah Ciganjur South Jakarta. This research is a qualitative research. Using primary and secondary data sources. Primary data sources are Akidah Akhlak teachers and students of MTs Daarussa'adah Ciganjur South Jakarta. Data collection techniques using interviews, observation and documentation. The results of the study that: The Akidah Akhlak teacher's strategy in overcoming negative behavior in students at MTs Daarussa'adah Ciganjur South Jakarta is that teachers always get used to good behavior to students and always provide good stimulus to students